Rhetorical exercises of Galileo - Sierotowicz, Tadeusz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2010)
The Assayer of Galileo Galilei is a classical text of the Italian literature. It was written in the context of discussions on comets and is a response, word by word, to the Libra astronomica ac philosophica signed by Lotario Sarsi but in fact written by Orazio Grassi. From the formal (i.e. rhetorical) point of view the Assayer is an example of the judicial, defensive speech. However, in the book one can also see the presence of the epideictic speech. The epideictic speech praises the methodological values of the Copernican vision of the universe, and blames those involved in the Aristotelian and Ptolemaic approaches. In the Assayer there is a very famous rhetorical period — the ending with the proverbial aut Caesar aut nihil — in which the internal connection between both types of speeches can be analysed. The rhetorical exercise developed in the present essay tries to disentangle the complex node of these speeches in this fragment.